Biomechanical assessment of anterior plate system, bilateral pedicle screw and transdiscal screw system for high-grade spondylolisthesis: a finite element study - Dhar, Utpal K.; Sultan, Hadi; Aghayev, Kamran; Tsai, Chi-Tay; Vrionis, Frank D. (Frontiers in Bioengineering and Biotechnology, 2024)
Limited information regarding the biomechanical evaluation of various internal fixation techniques for high-grade L5-S1 spondylolisthesis is available. The stiffness of the operated segment and stress on the hardware can profoundly influence clinical outcomes and patient satisfaction. The objective of this study was to quantitatively investigate biomechanical profiles of various fusion methods used for high-grade spondylolisthesis by using finite element (FE) analysis. An FE lumbar spine model of healthy spine was developed based on a patient's CT scan. High-grade (III-IV) spondylolisthesis (SP model) was created by sliding L5 anteriorly and modifying L5-S1 facet joints. Three treatment scenarios were created by adding various implants to the model. These scenarios included L5-S1 interbody cage in combination with three different fixation methodsthe anterior plate system (APS), bilateral pedicle screw system (BPSS), and transdiscal screw system (TSS). Range of motion (ROM), von Mises stress on cage, internal fixation as well as on the adjacent annuli were obtained and compared. The resistance to slippage was investigated by applying shear force on L5 vertebra and measuring its displacement regarding to S1. Under different loading conditions all treatment scenarios showed substantial reduction of ROM in comparison with SP model. No notable differences in ROM were observed between treatment models. There was no notable difference in cage stress among models. The von Mises stress on the internal fixation in the TSS model was less than in APS and BPSS. The TSS model demonstrated superior resistance to shear load compared to APS and BPSS. No discernible difference was observed between the SP, APS, BPSS, and TSS models when compared the ROM for adjacent level L4-L5. TSS's von Mises stress of the adjacent annulus was higher than in APS and BPSS. The TSS model exhibited biomechanical superiority over the APS and BPSS models.